Performance Management in Tax Administration: A Holistic Model for Malaysian Tax Authorities (Journal of Business Management and Accounting, 2018)
This paper has developed a holistic model for performance management in tax administration. To achieve this aim, the literature on performance management practice as well as performance management models were reviewed and analysed. Tax administration cannot perform efficiently and effectively without understanding performance management elements which include performance and governance evaluations. The performance management elements should also involve both internal and external stakeholders. The model in this paper is aimed at improving performance management in tax administration for Malaysian tax authorities